Developing a Deep Learning-Based Islamic Multicultural Education Model for Early Marriage Prevention among Students in Indonesian Vocational Pesantren - Mufarikha Rikha; Ahmad Ma’ruf; Saifulah (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2026)
Early marriage remains a significant social and educational challenge in Indonesia, particularly among adolescents in rural and pesantren-based communities. Despite legal reforms and various preventive initiatives, educational approaches that systematically integrate Islamic values, multicultural perspectives, and transformative pedagogy to address early marriage remain limited. Therefore, this study aimed to develop a Deep Learning-Based Islamic Multicultural Education Model (MPIM-DL) as a preventive educational strategy for early marriage among students in Indonesian vocational pesantren. This study employed a qualitative Research and Development (R&D) approach adapted from the Borg and Gall model. Data were collected through participant observation, semi-structured interviews, document analysis, and focus group discussions involving school principals, Islamic Religious Education teachers, guidance and counseling teachers, and students at SMK Pesantren Terpadu Kunjorowesi Ngoro. Data were analyzed using the interactive qualitative analysis model consisting of data condensation, data display, and conclusion drawing, while the trustworthiness of the findings was ensured through triangulation, member checking, and expert validation. The findings revealed that existing Islamic Religious Education primarily emphasized cognitive understanding of religious teachings with limited opportunities for reflective learning and critical decision-making regarding marriage readiness. In response, the developed MPIM-DL model integrates Islamic education, multicultural education, and the principles of Mindful Learning, Meaningful Learning, and Joyful Learning into a comprehensive instructional framework. The model demonstrated positive outcomes in enhancing students' understanding of the consequences of early marriage, strengthening multicultural awareness, fostering critical thinking, and promoting responsible life planning. This study contributes theoretically by extending the discourse on Islamic multicultural education through Deep Learning pedagogy and practically by providing an innovative instructional model for character education and early marriage prevention in vocational pesantren. Future studies are recommended to validate the model across broader educational contexts using longitudinal and mixed-methods approaches.